FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI BERWIRAUSAHA PETANI PENGOLAH GULA MERAH TEBU DI KABUPATEN AGAM - Annisa, Indah Febri; Melladia, Melladia; Muhelni, Leila (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
The objectives of this study are: (1) to determine the level of entrepreneurial interest among sugar palm farmers in Agam Regency; and (2) to identify the factors influencing the formation of entrepreneurial interest among these farmers. The research was conducted from April to May 2024. Agam Regency was selected as the research site due to its status as a central hub for palm sugar production in West Sumatra. This study employed a survey methodology. The sample consisted of 60 farmers who were members of Local Cooperative Groups (LKM). Respondents were selected using a combination of cluster sampling and simple random sampling techniques. A quantitative descriptive method was applied, and data were analyzed using Partial Least Squares (PLS).The results revealed that farmers affiliated with LKM exhibited a moderate level of entrepreneurial interest. The factors directly influencing the entrepreneurial intentions of LKM members are categorized as follows: belief in entrepreneurial interest, tendency to take action, need for new employment opportunities, and confidence in entrepreneurial feasibility. Both endogenous and exogenous factors affecting entrepreneurial intention among LKMA members include demographic characteristics, personality traits, psychological aspects, perceptions of LKMA, entrepreneurial abilities, surrounding environment, and social aspects. The structure of entrepreneurial intention accounts for 70% of the variance, as indicated by an R² value of 0.70. Keywords: Entrepreneurial Intention, Entrepreneurial Intention, Entrepreneurial Intention, Partial Least Squares (PLS)